Is the use of secukinumab after anti-TNF therapy greater than expected for the risk of developing inflammatory bowel disease? - Albayrak, Fatih; Gur, Mustafa; Karatas, Ahmet; Koca, Suleyman Serdar; Kisacik, Bunyamin (Elsevier Espana Slu, 2024)
Objective: In this study, our objective was to present real-life data on the incidence of inflammatory bowel disease (IBD) among patients receiving secukinumab treatment. Methods: The study consisted of 209 patients who had prior exposure to anti-tumor necrosis factor (TNF) or were biologically naive. Patients with a pre-existing history of IBD were excluded from the study. Results: Of the 209 patients in the study, 176 (84.3%) had ankylosing spondylitis, while 33 (15.7%) had psoriatic arthritis. 112 (53.6%) patients had prior exposure to at least one anti-TNF treatment before initiating secukinumab. IBD developed in 10 (4.8%) of the 209 patients. The incidence of IBD among patients who initiated secukinumab as their first biologic agent was 1%. For patients who had previously received any anti-TNF treatment and subsequently transitioned to secukinumab, the incidence of IBD was 8% (p = 0.018, odds ratio (OR): 8.38, 95% CI: 1.04-67.45). A mean of 3.67 months (+/- 4.3) after anti-TNF use, whereas IBD symptoms developed in the biologically naive patient after 15 months. Conclusion: Our study observed IBD incidence in 4.8% of patients using secukinumab. Patients who initiated secukinumab after previous anti-TNF treatment exhibited a significantly higher rate and risk of developing IBD. The onset of IBD occurred earlier in these patients (mean 3.67 months), whereas a single case of IBD showed a longer duration (15 months). Further studies with larger patient numbers are warranted to provide a more comprehensive understanding of our findings. (c) 2023 Elsevier Espana, S.L.U. and Sociedad Espanola de Reumatologia y Colegio Mexicano de Reumatologia. All rights reserved.
El uso de secukinumab tras la terapia anti-TNF es mayor de lo esperado por el riesgo de desarrollar enfermedad inflamatoria intestinal?
Keywords: Secukinumab; Inflammatory bowel disease; Ankylosing spondylitis; Psoriatic arthritis; Real-world data